Evaluation of vortex tube orifice percentage in terms of sediment trap efficiency in laboratory conditions - Asareh, Ali; Kamanbedast, Amirabbas (Tecnología y ciencias del agua, 2018)
Â Unfamiliarity with sedimentation problems in the basin has delayed a large number of projects in development, resulting in high costs. Different methods are used to prevent sediment from entering, which is transported by rivers in the form of bed load, and flows into the basin. These methods, which use vortex tubes, include increasing soil levels in the basin, building earthen walls or installing submerged panels to eliminate sediment from the inlets, and sediment traps, the use of vortex tubes. Since many variables are effective for retaining sedimentation and water loss with the vortex tube, the objective of this study was to evaluate the performance of vortex tubes in vitro, with a controlled discharge, and with four orifice widths/tube diameter (t/d) proportions (0.15, 0.20, 0.25, and 3.0), and a 45% angle with different discharges. The results showed that 43.2 kg of sediment were retained with a 0.25 t/d, which was equivalent to 84.16% of the total sedimentation that entered the system; and 36.02 kg of sediment were retained with a 0.3 t/d, which was equivalent to 84.43% of the total sedimentation that entered the system. With an increase in t/d, the retention of sediments will increase. For this index, the best option was t/d = 03. Nevertheless, if the supply of water in a region is extremely important and water is scarce, the discharge diverted with a t/d of 0.3 would be 13.88%, and 11.62% with a t/d of 0.25. Then the better option will be t/d = 0.25